2020
DOI: 10.1186/s12974-020-1727-6
|View full text |Cite
|
Sign up to set email alerts
|

CLEC14A deficiency exacerbates neuronal loss by increasing blood-brain barrier permeability and inflammation

Abstract: Background: Ischemic stroke is a main cause of mortality. Blood-brain barrier (BBB) breakdown appears to play a critical role in inflammation in patients with ischemic stroke and acceleration of brain injury. The BBB has a protective function and is composed of endothelial cells, pericytes, and astrocytes. In ischemic stroke treatments, regulation of vascular endothelial growth factor (VEGF)-A and vascular endothelial growth factor receptor (VEGFR)-2 is a crucial target despite adverse effects. Our previous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…We found that podocyte injury was further exacerbated in Clec14a knockout mice than those in control mice with ADR nephropathy. Moreover, CLEC14A deficiency exacerbated macrophage infiltration and inflammatory responses in the kidney from mice with ADR nephropathy in consistent with previous studies showing that the loss of CLEC14A increased inflammatory responses through adhesion molecule expression and glial cells activation in cerebral ischemia‐reperfusion injury 24 . Collectively, we conclude that CLEC14A as a central target molecule protects against podocyte injury.…”
Section: Discussionsupporting
confidence: 92%
“…We found that podocyte injury was further exacerbated in Clec14a knockout mice than those in control mice with ADR nephropathy. Moreover, CLEC14A deficiency exacerbated macrophage infiltration and inflammatory responses in the kidney from mice with ADR nephropathy in consistent with previous studies showing that the loss of CLEC14A increased inflammatory responses through adhesion molecule expression and glial cells activation in cerebral ischemia‐reperfusion injury 24 . Collectively, we conclude that CLEC14A as a central target molecule protects against podocyte injury.…”
Section: Discussionsupporting
confidence: 92%
“…The BBB is required for the structural stabilization of TJ proteins as structural com-ponents that maintain cerebrovascular integrity and BBB function [ 54 , 55 ]. Activated ROCK and pro-inflammatory cytokines correspond to vascular endothelial damage [ 51 , 56 ]. We found an inflammatory response that was upregulated by higher vascular permeability in the ischemic-injured brains of the VD group ( Figure 8 A–E).…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is a major cause of disability and death worldwide, but the agents currently used to treat stroke are not sufficient to effectively improve the recovery of stroke patients [ 25 , 26 ]. Coicis Semen, a traditional Chinese medicine, exerts antioxidant and anti-inflammatory effects in many diseases, including coronary heart disease [ 27 ], systemic inflammatory disease [ 28 ], and cancer [ 9 , 29 ].…”
Section: Discussionmentioning
confidence: 99%